Whole Cell Biosensor Using Anabaena torulosa with Optical Transduction for Environmental Toxicity Evaluation - Wong, Ling Shing; Lee, Yook Heng; Surif, Salmijah (Hindawi Publishing Corporation, 2013)
A whole cell-based biosensor using Anabaena torulosa for the detection of heavy metals (Cu, Pb, and Cd), 2,4- dichlorophenoxyacetate (2,4-D), and chlorpyrifos was constructed. The cyanobacteria were entrapped on a cellulose membrane through filtration. Then, the membrane was dried and fixed into a cylindrical well, which was designed to be attached to an optical probe. The probe was connected to fluorescence spectrometer with optical fibre. The presence of the toxicants was indicated by the change of fluorescence emission, before and after the exposure. The linear detection ranges for Cu, Pb, and Cd were 2.5–10.0 μg/L, 0.5–5.0 μg/L, and 0.5–10.0 μg/L, respectively, while 2,4-D and chlorpyrifos shared similar linear ranges of 0.05–0.75 μg/L. The biosensor showed good sensitivity with the lowest limits of detection (LLD) for Cu, Pb, Cd, 2,4-D and chlorpyrifos determined at 1.195 μg/L, 0.100 μg/L, 0.027 μg/L, 0.025 μg/L, and 0.025 μg/L, respectively. The overall reproducibility of the biosensor (n = 3) was <±6.35%. The biosensor had been tested with different combinations of toxicants, with the results showing predominantly antagonistic responses. The results confirmed that the biosensor constructed in this report is suitable to be used in quantitative and qualitative detections of heavy metals and pesticides.